2019
DOI: 10.3390/ani9121164
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Nutria (Myocastor coypus) in South Korea

Abstract: The nutria (Myocastor coypus) is an invasive alien species that have had major adverse effects on biodiversity and the agricultural economy in wetland habitats. Since 2014, the Ministry of Environment in South Korea has been carrying out the Nutria Eradication Project, and we investigated nutria distribution and genetic diversity of nutria populations in South Korea. We estimated that 99.2% of nutria habitats are in the mid-lower Nakdong River regions. To further analyze the genetic diversity in eight major nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…M. coypus populations can decline owing to adverse effects in natural environments with temperatures ranging between 0–5 °C 14 . In extreme cold, they fail to reproduce and often show high mortality (≤ 71%) when sheet ice forms on water bodies 1 , 24 , 25 . The Nakdong River, located in the southeastern region of South Korea, maintains relatively warm temperatures year-round, and has notably warm winters compared to the rest of the country; whereas, the other major rivers, such as the Han and Geum Rivers, are located in cold-temperature and temperate regions, respectively, with recorded winter temperatures < − 26.2 °C (KMA 2021, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. coypus populations can decline owing to adverse effects in natural environments with temperatures ranging between 0–5 °C 14 . In extreme cold, they fail to reproduce and often show high mortality (≤ 71%) when sheet ice forms on water bodies 1 , 24 , 25 . The Nakdong River, located in the southeastern region of South Korea, maintains relatively warm temperatures year-round, and has notably warm winters compared to the rest of the country; whereas, the other major rivers, such as the Han and Geum Rivers, are located in cold-temperature and temperate regions, respectively, with recorded winter temperatures < − 26.2 °C (KMA 2021, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Myocastor coypus is a large, semiaquatic rodent indigenous to the subtropical and temperate regions of South America 1 and is currently included on the International Union for Conservation of Nature (IUCN) list of the 100 worst invasive global species 2 . M. coypus was introduced to North America, Europe, Asia, and Africa for meat and fur production 3 – 5 ; however, because of the decreasing demand and the consequential reduced market price, individuals were either released or escaped from farmhouses, and wild populations have since established in natural environments 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…South Korea: after the abandonment of farms thousands of coypus escaped and established mostly in the Nakdong River basin area (Kim et al 2019b). The government established a 9.5-million-USD eradication program in 2014 which is showing the first mild results (Kim et al 2019a).…”
Section: East Asiamentioning
confidence: 99%
“…The fixation index (F ST ) is a widely used genetic distance measure for genetic differentiation [50] which occurs when gene flow between populations is restricted. Pairwise F ST values of eight nutria populations in the Nakdong River Basin of South Korea, comprised of 93 individuals each typed at 12 microsatellite loci, were obtained from the study by Kim et al [28] (Fig 2B). These authors reported that variation in F ST values was not explained by pairwise Euclidean distance (i.e., isolation-by-distance, IBD).…”
Section: Gene Flow and Isolation Modelingmentioning
confidence: 99%
“…Some studies have related the occurrence of nutrias with environmental factors such as climate and topographic conditions to predict habitat suitability [24][25][26] or have investigated the distributional shifts of nutria populations [20,26,27]. Other studies have characterized the structure and genetic diversity of nutria populations for management purposes [28,29]. However, no comprehensive study has yet examined the gene flow and habitat connectivity of nutria populations as well as their habitat distribution, which can serve as a key functional element in the development of spatial management plans and strategies for nutria control.…”
Section: Introductionmentioning
confidence: 99%